Upaya Kantor Urusan Agama Dalam Meminimalisir Pernikahan Dini - Siregar, Siti Suriani; Ahmatnijar, Ahmatnijar (Jurnal El-Thawalib, 2024)
This research examines the implementation of early marriages in North Padangsidimpuan District, Padangsidimpuan City and the efforts of the religious affairs office in minimizing early marriages in the District. The research method used is field research with a qualitative approach. The primary data sources in this research are the Head of the North Padangsidimpuan District Office of Religious Affairs, religious leaders and people who enter into early marriages. While secondary data was collected through several references such as books, laws and journals that were considered relevant to this research. Data collection techniques with interviews and documentation with qualitative descriptive data analysis techniques. Based on the research results obtained, namely to carry out early marriages in North Padangsidimpuan District, there are procedures to be followed so that the marriage is legal in the eyes of religion and in the eyes of the law. Such as submitting a marriage dispensation to the Padang Sidempuan Religious Court, obtaining a marriage license, providing a copy of the dispensation decision to the religious affairs office, notification of the will to marry, examination of the will for marriage, announcement of the will for marriage, and implementation of the marriage contract. Then the KUA's efforts to prevent early marriage in Padang sidempuan Utara District are checking the administrative completeness of the two prospective brides, conducting outreach to the community, youth and parents and socializing law number 16 of 2019. It is proven by the KUA's efforts that the number Underage marriages are decreasing every year. Namely, from 2020 to 2022 there will be 16 underage marriages, with details of 5 underage men and 11 women. Then in 2020 there will be 11 people, in 2021 there will be 4 people and in 2022 there will be 1 person.